CeO2 nanoparticles synthesized by a microwave-assisted hydrothermal method: evolution from nanospheres to nanorods - Araujo, V. D.; Avansi, W.; de Carvalho, H. B.; Moreira, M. L. [UNESP]; Longo, Elson [UNESP]; Ribeiro, C.; Bernardi, M. I. B. (Royal Soc Chemistry, 2012)
Ceria (CeO2) plays a vital role in emerging technologies for environmental and energy-related applications. The catalytic efficiency of ceria nanoparticles depends on its morphology. In this study, CeO2 nanoparticles were synthesized by a microwave-assisted hydrothermal method under different synthesis temperatures. The samples were characterized by X-ray diffraction, transmission electron microscopy, Raman scattering spectroscopy, electron paramagnetic resonance spectroscopy and by the Brunauer-Emmett-Teller method. The X-ray diffraction and Raman scattering results indicated that all the synthesized samples had a pure cubic CeO2 structure. Rietveld analysis and Raman scattering also revealed the presence of structural defects due to an associated reduction in the valence of the Ce4+ ions to Ce3+ ions caused by an increasing molar fraction of oxygen vacancies. The morphology of the samples was controlled by varying the synthesis temperature. The TEM images show that samples synthesized at 80 degrees C consisted of spherical particles of about 5 nm, while those synthesized at 120 degrees C presented a mix of spherical and rod-like nanoparticles and the sample synthesized at 160 degrees C consisted of nanorods with 10 nm average diameter and 70 nm length. The microwave-assisted method proved to be highly efficient for the synthesis of CeO2 nanoparticles with different morphologies.